The 2024 General Elections in Indonesia: Issues of Political Dynasties, Electoral Fraud, and The Emergence of A National Protest Movements - Hidayat, M. Miftahul (Yayasan Irwan Abdullah Cendekia, 2024)
This research aims to explain the phenomenon of political dynasties, electoral fraud, and protest movements during the 2024 General Elections in Indonesia. By using a qualitative descriptive method, this research focuses on aspects related to the main factors of the emergence of political dynasties, electoral fraud, and protest movements in the 2024 election based on secondary data obtained from online news sources. Data collection process was carried out through reading the news articles using the keywords “political dynasties”, “electoral fraud”, “protest movements”, and “2024 General Elections”. Data analysis was conducted through content analysis of news texts to obtain accurate data, descriptive insights and thematically explore the data inductively. The findings in this study show that the issues of political dynasties, electoral fraud, and the national protest movements in the 2024 General Elections are a series of interconnected phenomena. In addition, this study also reccomends further research on the importance of understanding public perceptions of political dynasties, the issue of electoral fraud, and protest actions against active voters in the 2024 General Elections using an empirical approach.